Juridical Analysis of Electronic Agreement Validity in Online Loans Under Electronic Information and Transactions - Alex Candra; Anto Kustanto; Takwim Azami (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study examines the validity of electronic consent in online loan agreements according to Indonesian laws and regulations, specifically Law Number 11 of 2008 concerning Electronic Information and Transactions and its amendments in Law Number 19 of 2016. Electronic consent, such as the “click agree” mechanism in online loan applications, is legally recognized if it is made consciously by the user, through a reliable and secure electronic system, and in accordance with the principles of prudence and honesty as stipulated in Article 1320 of the Civil Code and Article 15 of the Electronic Information and Transactions Law. However, implementation in the field still faces obstacles, including low legal and digital literacy among the public. In cases of default, agreements remain subject to general civil law, with electronic evidence valid under Article 5 of the ITE Law. This research uses a normative-juridical approach through a literature review, combining legislative, conceptual, and case studies to analyze the legal framework, implementation, constraints, and implications of electronic consent. The results emphasize the importance of regulatory harmonization, electronic signature certification, and digital legal education to create legal certainty and optimal consumer protection.